How would able-bodied children perceive a student with an intellectual disability in inclusive physical education? - Nemček, Dagmar (Specijalna edukacija i rehabilitacija, 2024)
Introduction. The views of able-bodied children on the inclusion of a student with intellectual disabilities in physical education classes are one of the factors influencing the success of the physical education process. The social interactions of able-bodied pupils and pupils with disabilities are crucial in creating a positive classroom climate. Objectives. The aim of the study was to assess the attitudes of able-bodied children towards the inclusion of pupils with intellectual disabilities in physical education lessons and compare the differences between boys and girls. Methodes. The study involved 274 able-bodied pupils, 153 boys (mean age 12.34±1.19 years) and 121 girls (mean age 12.45±1.23 years). A modified Czech version of the CAIPE-R for the inclusion of a student with an intellectual disability was used (α=.797). Differences between boys and girls were assessed by the Mann-Whitney U-test. Differences between attitudinal dimensions were calculated using the Wilcoxon Signed Rank test. Results. Both genders of able-bodied children (boys, 2.91±.45 score; girls, 3.11±.40 score) assessed the inclusion of a student with an intellectual disability in physical education classes rather positively. Girls were more positive to include a student with an intellectual disability than boys, which was reflected in their overall (U=6984, p=.00, r=.22) and sport-specific attitudes (U=6335, p=.00, r=.28). Boys assessed general attitudes more positively than sportspecific attitudes (Z=-4.97, p=.00, r=.24). Conclusion. More information about the attitudes of intact classmates, teachers, and school management toward inclusion needs to be gathered through research monitoring.
Keywords: students with intellectual disability; able-bodied children; attitudes; inclusive education; inclusive physical education